The twelve labors of Hercules - Saunders, Nick. (Milwaukee, WI : World Almanac Library, 2007)
Presents a graphic novel that tells the ancient Greek legend of Hercules and his amazing strength.
Originally published: Roma : "Erma" di Bretschneider, c1992.
Includes bibliographical references (p. 47) and index.
Library Media Connection.
Library Media Connection, November 2007.
3.9
5-8
Keywords: Heracles (Greek mythology) -- Comic books, strips, etc. -- Juvenile literature; Mythology, Roman; Cartoons and comics; Heracles (Greek mythology) -- Cartoons and comics; Mythology, Roman; Comic books, strips, etc; Greek mythology; Heracles (Greek mythology) -- Comic books, strips, etc